Association Between Waist Circumference and Dementia in Older Persons: A Nationwide Population‐Based Study. Issue 11 (5th November 2019) - Cho, Geum Joon; Hwang, Soon Young; Lee, Kyu‐Min; Choi, Kyung Mook; Hyun Baik, Sei; Kim, Tak; Han, Sung Won; Yoo, Hye Jin
Abstract : Objective: This study examined whether a positive association exists between waist circumference (WC) and dementia among older persons. Methods: The study population comprised 872, 082 participants aged 65 years and older who participated in a Korean national health screening examination between January 1, 2009, and December 31, 2009. Adjusted hazard ratios and 95% CIs for dementia during follow‐up from 2009 to 2015 were calculated according to baseline BMI and WC categories. Results: After a multivariate adjustment that included BMI, the hazard ratios for dementia showed a stepwise increase according to the increase in WC categories by 5 cm from 85 to 90 cm in men and from 80 to 85 cm in women until ≥ 110 cm (from 1.06 [95% CI: 1.03‐1.09] to 1.64 [95% CI: 1.37‐1.94] in men and from 1.04 [95% CI: 1.02‐1.07] to 1.58 [95% CI: 1.36‐1.84] in women). The influence of the current WC category for abdominal obesity on the risk of dementia was different according to BMI; especially, the normal weight men and women with abdominal obesity had a prominent increased risk of dementia compared with those without abdominal obesity. Conclusions: Abdominal obesity, as measured by WC, was associated with significantly increased risk of dementia after adjustment for general obesity.